Teucrium scorodonia (Lamiaceae) – a neglected species of the Ukrainian flora (CHORNOMORSKI BOTANICAL JOURNAL, 2025)
Question: What are the morphological, chorological, ecological and coenotic features of the newly discovered localities of Teucrium scorodonia in Ukraine? Location: Zacharovanyi Krai National Nature Park and its outskirts, Khust district, Zakarpattia oblast, Ukraine. Methods: morphological description, field survey, phytoindicative assessment Nomenclature: vascular plants – POWO, syntaxa – FloraVeg.EU, Pladias Results: On August, 2024, we discovered a species that has not been previously reported in the main fundamental publications on the flora of Ukraine – Teucrium scorodonia. The representatives of this species were found on the southern megaslope of the Velykyi Dil ridge. On August 2025 we confirmed the above locality and revealed two new localities of the species in the same national nature park. A detailed analysis of literature and herbarium materials showed that this species has existed in the flora of Ukraine for at least the last 80 years, but these facts were not taken into account when preparing fundamental floristic publications on the territory of Ukraine. Therefore, T. scorodonia received de facto status as a neglected species of the Ukrainian flora. Teucrium scorodonia is a European species with a sub-Atlantic distribution, scattered in Southern, Western, and Central Europe, with the northern limit of its continuous distribution reaching south Sweden and Norway, and the eastern limit includes isolated localities in Poland and east Hungary on the border with Ukraine. Most of the newly discovered populations of the species in Eastern Europe, particularly in Poland, are considered anthropogenic. In neighboring Slovakia and Czechia, however, the species is under protection. The communities where the species was recorded in Ukraine belong to three different associations of classes Calluno-Ulicetea, Nardetea, and Epilobietea. The localities we found belong to the R1M and R54 habitat types. The phytoindicative assessment of the habitats according to the Ellenberg Indicator Values showed that compared to the optimal conditions of the communities described in Slovakia and Spain, the localities of the species in Ukraine are characterized by cooler, wetter, and more acidic conditions. Conclusions: Our findings of Teucrium scorodonia on the territory of the Zacha-rovanyi Krai National Nature Park can be considered the currently confirmed easternmost localities of the species in Eastern Europe. Considering the relatively low level of anthropogenic, in particular, tourist impact on the studied localities, the natural expansion of T. scorodonia to this territory is quite probable. Further observations of the discovered localities, as well as searching for new localities of the species in Ukraine, may shed light on its ecological and coenotic preferences and origin.
Keywords: biodiversity, chorology, Ellenberg Indicator Values, EUNIS, habitat, morphology, population, syntaxonomy, Ukraine, “Zacharovanyi Krai” National Nature Park, Zakarpattia oblast